Diagnosis and Management of Autoimmune Inner Ear Disease - Muhammad Arifudin; Rossy Rosalinda (Jurnal Otorinolaringologi Kepala dan Leher Indonesia, 2026)
Diagnosis and Management of Autoimmune Inner Ear Disease Background: Autoimmune Inner Ear Disease is an autoimmune disease of sensorineural hearing loss, with an incidence of less than 1% worldwide. Symptoms of Autoimmune Inner Ear Disease often resemble the symptoms of other types of sensorineural hearing loss, making the diagnosis difficult. Objective: To understand all aspects of Autoimmune Inner Ear Disease. Literature Review: Autoimmune Inner Ear Disease is a rare autoimmune disease characterized by progressive and fluctuating sensorineural hearing loss. Autoimmune Inner Ear Disease is more common in women, aged between 20 and 50 years. Autoimmune Inner Ear Disease can be primary or secondary. The mechanism of Autoimmune Inner Ear Disease can be damage mediated by autoantibodies, immune complex deposition, T-cell inflammation. Typical symptoms and signs include bilateral sensorineural hearing loss, tinnitus, sometimes vestibular disorders and response to corticosteroid treatment. Complete blood count, erythrocyte sedimentation rate, antinuclear antibodies, and other immunological profiles can confirm the diagnosis. Magnetic resonance imaging was performed to rule out retrocochlear pathology and demyelination. High-dose corticosteroids are the first-line treatment. Conclusion: Autoimmune Inner Ear Disease is an autoimmune disease characterized by progressive sensorineural hearing loss, which may be accompanied by tinnitus and vestibular disorders. Corticosteroids are the first-line treatment.